Pelatihan Budidaya Ikan Lele Kolam Terpal Di Kecamatan Seberang Musi Kabupaten Kepahiang - Muhammad Subhan Hamka; Andika Prawanto; Ikromatun Nafsiyah; Maisya Zahra Al Banna; Widiastini Arifuddin; Arif Rahman Azis (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Seberang Musi sub-district launched a food security program through catfish farming using tarpaulins in 2020. This is one way for the sub-district government to socialize household-scale fish farming, especially catfish commodities, so that people get additional income benefits by utilizing the yard around the house. The problems that exist in the residents of Talang Babatan Village and Benuang Galing Village are the lack of technical skills in fish farming, because both villages are villages that produce plantation products. Therefore, the service team was invited to provide training in an effort to succeed the village development program. In addition to being an effort to alleviate poverty in rural communities, and accelerate poverty alleviation programs in rural areas. The purpose of this activity is to provide training in catfish farming in tarpaulin ponds as well as a medium for disseminating knowledge and transferring technology through community service activities. The methods used were: 1. counseling to participants about catfish farming in tarpaulin ponds; 2. demonstration of methods and practices by giving examples of how to assemble tarpaulins as maintenance containers and how to handle fish directly to participants; 3. evaluation. The collected data were tabulated and analyzed using descriptive analysis method. The purpose of the evaluation was to assess the response of participants in the transfer of knowledge and skills. This was done by assessing the results of the initial and final questionnaires filled out by the participants. The results of the questionnaire showed that there was an increase in participants' knowledge by 12.5% with a minimum value in the pre-test of 37.5 and a maximum value of 87.5 while the minimum value in the post-test was 50.0 and a maximum value of 87.5.